Dynamic behaviour of a suspended bubble and its influence on the distribution of electric fields in insulating oil of an on-load tap-changer within power transformers. (February 2023) - Liu, Chenlei; Zhao, Tong; Sun, Ying; Wang, Xiaolong; Cao, Shi
Highlights: The paper provides a reference to purification and filtration measures for insulating oil in OLTC. This paper analysed the internal structure and operating principle of the OLTC switching core and clarified the electric field distribution of each component under actual working conditions. The paper clarifies the coupling mechanism between the moving bubbles and the electric field distribution to assess the insulation performance of the OLTC. By constructing a two-phase flow model based on the OLTC structure, the paper investigated the global dynamics of small bubbles in the OLTC under the combined action of flow and electric fields and generalized the mechanism of their influence on the spatiotemporal distribution of the electric field inside the OLTC. Abstract: A small amount of gas bubbles generated in an on-load tap changer (OLTC) can cause partial discharges in the intense electric field region, which severely threaten the safe operation of the device. It is crucial to clarify the coupling mechanism of moving bubbles together with the electric field distribution in the OLTC. This paper analyzed the internal structure and operating principle of the OLTC switching core and clarified the electric field distribution of each component under working conditions. A 2D two-phase flow model was established based on a practical OLTC structure by using the phase-field method. We investigated the global dynamics of small bubbles in the OLTC under the combined action of flow and electric fields and generalized the mechanism of their impact on the spatiotemporal distribution of the electric field inside the OLTC. Finally, the influence of the characteristic parameters of the bubbles and the insulating oil on the insulation property of the OLTC were clarified. The results showed that the distribution of the electric field was closely related to the shapes of the bubbles and the initial field strength. When the oil quality was poor, there was a risk that the bubbles caused partial discharge, in which case, oil purification and filtration operations should take place. The oil flow velocity should be controlled within a specific range to ensure that the rapid passage of bubbles through the intense electric field area does not render distortions in the field strength significant. The smaller the bubble size is, the steeper the gradient of electric field becomes at the gas-oil interface, and the greater the field strength inside the bubble, more likely to cause the occurance of accidental discharges in the OLTC.